Perlindungan Hukum Kepada Kreditur Dalam Perjanjian Kredit Dengan Jaminan Hak Tanggungan - Pusnia Abdul Munsir; Merry Tjoanda; Ronald Fadly Sopamena (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: In order to make ends meet, humans need to work and try, one of which is by starting their own business, for businesses, capital is needed and in obtaining capital, one of them is by making loans to banks. Default, the creditor has the right to execute the collateral in accordance with the provisions of Law No. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land. Even though the creditor's rights have been stipulated in the law, however, when the debtor defaults and when the execution process is ongoing, the debtor fights against the creditor which results in the execution process being delayed and because of this it causes the creditor to suffer losses. The purposes of this study are: To find out and explain how the position of the creditor is in a credit agreement with a mortgage guarantee, To find out and explain how the legal protection for creditors is in a credit agreement with a mortgage guarantee. The method used in this research is normative juridical. And using a statutory approach as well as a conceptual approach, with legal materials consisting of primary, secondary and tertiary legal materials which are analyzed qualitatively. The results of this study indicate that the position of the creditor in the credit agreement with collateral rights has been regulated in the provisions of Article 1 point 1 of Law no. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land, based on the explanation of the article that the creditor's position in the Mortgage Right is to have a priority position and has the right to precede other creditors in paying off debts. And creditors who have prior rights are also called Preference Creditors. There are two types of legal protection for creditors, namely preventive legal protection which aims to prevent problems or violations by giving a warning in carrying out an obligation. And repressive legal protection is a last resort in the form of sanctions such as fines, imprisonment, and additional penalties given when a dispute has occurred or a violation has been committed.